Bare Necessities : Essential Life Skills For Surviving In The Real World - Jemma Wayne
So you've left home and you are living your new independent life but then you need to switch on the washing machine or change a tyre and no one has ever shown you how. Bare Necessities is the invaluable book for big kids of all ages. Guiding you through everything from how to write a cheque, to filling out tax returns, and from boiling an egg to contacting the gas company when the egg fails to boil - it is essential reading for all adult-novices. It is broken down into sections according to lie skills and these food, health, housekeeping, car survival, banking, starting work and property. No longer will you have to phone your friends to ask how to do things or sit through lectures on how to change a plug. You now have it all at your fingertips.